RELAPSE AFTER ORTHODONTIC TREATMENT - Aurellia, Syifa Callista; Dermawan, Tara Marie; Akifah, Tasha Farah; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2024)
Orthodontic treatment results are prone to relapse over time, which is the unfavorable change in position of teeth to its original position before orthodontic treatment. With that said, retention is an important part of almost every case of orthodontic treatment. There are many contributing factors to the incidence of a relapse. This article aims to explain the incidence and prevention of relapse after orthodontic treatment through reviewing literature published during 2012 to 2022 which discusses topics that are appropriate and related to relapse and retention. Sources were taken from textbooks, journals and websites that can be accessed through Google Scholar and PubMed databases. A total of 30 references were found, and 9 articles were included in the integrative review after further analysis. This article concludes that relapse is a common occurrence after orthodontic treatment because of gingival and periodontal factors, occlusal factors, soft tissue factors, hard tissue factors, and growth factors, and its prevention requires the use of retainers, either removable or fixed, depending on the case.